Controlled venospasm-assisted foam sclerotherapy combined with high ligation—a novel minimally invasive approach for primary great saphenous vein varicosities - Ya, Chen; Zechao, Liu; Xuchang, Zhu; Boyu, Chen; Zhengli, Liu; Jie, Kong (Frontiers in Surgery, 2026)
PurposeThis study aimed to evaluate the efficacy and safety of Controlled Venospasm-Assisted Foam Sclerotherapy (CVAFS) combined with high ligation (HL) for treating primary great saphenous vein (GSV) varicosities.Materials and methodsA retrospective cohort of 127 patients with primary GSV varicosities underwent CVAFS with high ligation between 1 Jan 2023 and 1 October 2023. Venospasm was induced by rotational mechanical stimulation of the catheter combined with external compression, resulting in a transient reduction of vessel diameter by 50%–70%, followed by DSA (Digital subtraction angiography)-guided foam injection (1:4 liquid-to-gas ratio). Technical success was defined as complete procedural execution under imaging guidance. Primary endpoints included 1-year GSV occlusion rate (assessed by duplex ultrasound) and reduction in Venous Clinical Severity Score (VCSS). Complications were recorded and managed conservatively.ResultsTechnical success was achieved in 100% of limbs (145/145). Among 127 enrolled patients, 109 patients (125 limbs) completed the 12-month follow-up, yielding a follow-up rate of 85.8% (109/127). At 12 months, 93.6% of great saphenous veins (117/125 limbs) maintained complete occlusion. The Venous Clinical Severity Score (VCSS) significantly decreased from 6.18 ± 3.90 preoperatively to 0.86 ± 0.90 postoperatively (V = 7,875, p < 0.001). Thrombophlebitis observed in 9.6% of limbs (12/125), all cases resolved spontaneously within 2 weeks with conservative management (warm compression and NSAIDs). Saphenous Junction Pain occurred in 32.8% of limbs (41/125), with complete resolution within 2 weeks without intervention. No deep venous thrombosis (DVT), pulmonary embolism, skin necrosis, or neurological injuries were documented.ConclusionCVAFS leverages controlled venospasm to enhance foam-endothelium contact, significantly improving occlusion rates and symptom relief with acceptable safety. This approach offers a promising minimally invasive alternative for GSV varicosities.